2006
DOI: 10.1007/s11103-006-9058-2
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of the maize and Arabidopsis thaliana caffeic acid O-methyl-transferase genes by two new maize R2R3-MYB transcription factors

Abstract: The maize (Zea mays L.) caffeic acid O-methyl-transferase (COMT) is a key enzyme in the biosynthesis of lignin. In this work we have characterized the involvement of COMT in the lignification process through the study of the molecular mechanisms involved in its regulation. The examination of the maize COMT gene promoter revealed a putative ACIII box, typically recognized by R2R3-MYB transcription factors. We used the sequence of known R2R3-MYB factors to isolate five maize R2R3-MYB factors (ZmMYB2, ZmMYB8, ZmM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
117
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(124 citation statements)
references
References 55 publications
4
117
1
Order By: Relevance
“…In contrast, no orthologs corresponding to the MYB factors AtMYB58 or AtMYB63 directly implicated in the regulation of lignin biosynthesis (Zhou et al, 2009) were differentially regulated. We also identified a MYB TF transcript that was significantly more abundant in stem outer tissues and belongs to subgroup 4, which includes repressors of the lignin biosynthetic pathway such as AtMYB4, EgMYB1, and ZmMYB31/42 (Jin et al, 2000;Fornalé et al, 2006Fornalé et al, , 2010Legay et al, 2010). Although functional analyses are obviously necessary, the expression of a potential lignin repressor in outer tissues is consistent with the hypolignified nature of this tissue.…”
Section: Hypolignification In Flax Stems Involves Differential Expresmentioning
confidence: 57%
“…In contrast, no orthologs corresponding to the MYB factors AtMYB58 or AtMYB63 directly implicated in the regulation of lignin biosynthesis (Zhou et al, 2009) were differentially regulated. We also identified a MYB TF transcript that was significantly more abundant in stem outer tissues and belongs to subgroup 4, which includes repressors of the lignin biosynthetic pathway such as AtMYB4, EgMYB1, and ZmMYB31/42 (Jin et al, 2000;Fornalé et al, 2006Fornalé et al, , 2010Legay et al, 2010). Although functional analyses are obviously necessary, the expression of a potential lignin repressor in outer tissues is consistent with the hypolignified nature of this tissue.…”
Section: Hypolignification In Flax Stems Involves Differential Expresmentioning
confidence: 57%
“…9,12,16,21 In addition, some MYBs have been suggested to function as repressors in fine-tuning the expression level of phenylpropanoid biosynthetic genes. [46][47][48][49][50] Identification and characterization of all the cis elements and transcription factors involved in regulation of lignin biosynthesis will be essential for gaining a full picture of the complexity of transcriptional control of lignin biosynthesis. Second, little is known about how lignin heterogeneity is regulated at the transcription level.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Several studies have identified different regulators of lignin biosynthesis in grasses (reviewed in Gray et al, 2012), such as maize (Zea mays) MYB31 and MYB42, two subgroup 4 R2R3-MYB transcription factors that act as repressors of the lignin pathway (Fornalé et al, 2006(Fornalé et al, , 2010Sonbol et al, 2009). Despite their different roles in lignin regulation, both factors repress the maize caffeic acid O-methyl transferase (comt) gene (AC196475).…”
Section: Introductionmentioning
confidence: 99%
“…Despite their different roles in lignin regulation, both factors repress the maize caffeic acid O-methyl transferase (comt) gene (AC196475). Mutations in this gene have been shown to produce the brown midrib3 phenotype (Vignols et al, 1995;Fornalé et al, 2006Fornalé et al, , 2010. The expression of maize comt is induced by wounding (Capellades et al, 1996) through a mechanism that remains unknown, while it has been demonstrated that the wound induction of the Arabidopsis thaliana COMT is CORONATINE-INSENSITIVE PROTEIN1 COI1 dependent (Reymond et al, 2000).…”
Section: Introductionmentioning
confidence: 99%